Advanced Surgical Approaches for the Rejuvenation of the Submental and Cervicofacial Regions: A Literature Review for a Personalized Approach - Anastasiya S. Borisenko; Valentin I. Sharobaro; Nigora S. Burkhonova; Alexey E. Avdeev; Yousif M. Ahmed Alsheikh (Cosmetics)
The quest for surgical advancements regarding the enhancement of the submental and cervicofacial regions has witnessed a remarkable upsurge in recent years. Informed patients are actively seeking sophisticated plastic surgery techniques to achieve comprehensive rejuvenation in these specific areas. Common complaints expressed by these patients include sagging of the jawline, the emergence of deep perioral wrinkles, and the formation of “marionette lines” within the lower third of the face. Furthermore, the manifestation of age-related signs, including neck laxity, submental adipose accumulation, “witch’s chin” deformity, and weakened platysma musculature, are common within this anatomical region. This literature review aims to summarize recent technical improvements, historical evolution, indications, postoperative care, and challenges for facial rejuvenation of the lower third of the face and neck. The application of minimally invasive procedures as part of a comprehensive approach for an aging face will also be discussed. In this article, an extensive search of the available literature was conducted using leading databases, including PubMed and MEDLINE, with the keywords “neck lift”, “platysmaplasty”, “facial rejuvenation”, “medial platysmaplasty”, “lateral platysmaplasty”, “neck rejuvenation”, and “cervicofacial rejuvenation”.